2008
DOI: 10.1016/j.canlet.2007.11.016
|View full text |Cite
|
Sign up to set email alerts
|

N-(4-Hydroxyphenyl)retinamide induced differentiation with repression of telomerase and cell cycle to increase interferon-γ sensitivity for apoptosis in human glioblastoma cells

Abstract: Glioblastoma is the most malignant and prevalent brain tumor in humans. It is composed of heterogenic abnormal astroglial cells that avoid differentiation, maintain proliferation, and reluctant to apoptosis. N-(4-Hydroxyphenyl) retinamide (4-HPR) induced astrocytic differentiation and increased sensitivity to interferon-gamma (IFN-γ) for apoptosis in human glioblastoma A172, LN18, and SNB19 cells. Combination of 4-HPR and IFN-γ significantly inhibited human telomerase reverse transcriptase (hTERT), cyclin depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…2). It is known that IFNγ induces caspases 3, 8 and 9 in certain cell lines, including glioblastoma and conjunctival epithelial cells (26,27). In the present study, we demonstrated that IFNγ induced these caspases in HCC cells, and that their activation was enhanced by β-catenin overexpression.…”
Section: Discussionsupporting
confidence: 67%
“…2). It is known that IFNγ induces caspases 3, 8 and 9 in certain cell lines, including glioblastoma and conjunctival epithelial cells (26,27). In the present study, we demonstrated that IFNγ induced these caspases in HCC cells, and that their activation was enhanced by β-catenin overexpression.…”
Section: Discussionsupporting
confidence: 67%
“…The cells were then washed twice with PBS, pH 7.4 before being fixed in 95% ethanol. The cells were allowed to dry before Wright staining [21]. Finally, the morphological features of the cells (n=300) were observed under the light microscope, as we described recently [21].…”
Section: Methodsmentioning
confidence: 99%
“…The cells were then washed twice with PBS, pH 7.4, before Wright staining. The 6-well plates were then allowed to dry and examined under the light microscope, as we reported previously (Janardhanan et al, 2008). The morphological features of apoptotic cells included at least one of such characteristics as cell shrinkage, chromatin condensation, and membrane-bound apoptotic bodies.…”
Section: Methodsmentioning
confidence: 99%